Epidemiology of brain and spinal tumors - Moini, Jahangir (Academic Press, 2021)
Epidemiology of Brain and Spinal Tumors provides a single volume resource on imaging methods and neuroepidemiology of both brain and spinal tumors. The book covers a variety of imaging techniques, including computed tomography (CT), MRI, positron emission tomography (PET), and other laboratory tests used in diagnosis and treatment. Detailed epidemiology, various imaging methods, and clinical considerations of tumors of the CNS make this an ideal reference for users who will also find diverse information about structures and functions, cytology, epidemiology (including molecular epidemiology), diagnosis and treatment. This book is appropriate for neuroscience researchers, medical professionals and anyone interested in a complete guide to visualizing and understanding CNS tumors.